Microstructure and properties of FeCrMoVC tool steel produced by selective laser melting. (5th January 2016) - Sander, J.; Hufenbach, J.; Giebeler, L.; Wendrock, H.; Kühn, U.; Eckert, J.
Abstract: This paper demonstrates the successful processing of a high-strength Fe85Cr4Mo8V2C1 tool steel by selective laser melting (SLM). Based on tailored parameter variation studies, crack-free and highly dense FeCrMoVC parts (99.99% relative density) are obtained by this processing method. The applied localized high heat inputs during very short interaction times result in a fine, homogeneous microstructure composed of martensite, austenite, and carbides. This combination of phases together with the morphology of the microstructure results in excellent mechanical properties, such as a microhardness of 900 HV 0.1 (ca. 67 HRC) and a compressive strength of about 3800 MPa combined with a fracture strain up to 15%. Therefore, the SLM processing of this alloy enables a further increase of the hardness and compressive strength compared to the as-cast state. Altogether, processing the FeCrMoVC steel by SLM as one key additive manufacturing technology shows high potential for advanced tool design. Graphical abstract: Highlights: High-strength Fe85Cr4Mo8V2C1 tool steel was successfully processed by SLM. Crack-free and highly dense parts (99.99% relative density) were obtained. Mechanical properties are improved compared to the as-cast state. Microhardness 900 HV0.1, compression strength 3800 MPa, fracture strain up to 15%.